On the role of productive government spendings for convergence of a growing economy with heterogenous specialists - Ingrid Ott; Susanne Soretz (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2010)
This paper employs a dynamic framework to compare the effects of alternative government activities on convergence of industrialized economies to the technology frontier. The government's Instruments include facilitating private investment and education policy. The latter enhances skills of heterogenous specialists and imply the decision on their respective shares. The analysis distinguishes between an isolated policy of a single economy and coordinated policies of various countries. Which policy maximizes the speed of convergence is crucially affected by the economy's state of development. A policy switch between the mentioned instruments while catching-up may be preferable.
urn:nbn:de:swb:90-197740
Keywords: O31; O33; O38; J24; L26; 330; Education policy; amount and structure of public expenditure; highlyskilled specialists; Bildungspolitik; Öffentliche Bildungsausgaben; Investitionspolitik; Wachstumspolitik; Wachstumstheorie; Hochqualifizierte Arbeitskräfte; Entwicklungskonvergenz; Theorie